Preharvest Technology of information systems in Deli Serdang - Elfani Oktianto; Saipul Bahri Daulay; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Preharvest Technology of Information systems in Deli Serdang regency was done manually, resulting in ineffective and inefficient information storage and processing systems. More than that, the information seekers-and decision-makers also have difficult in obtaining the data they need. Therefore it is necessary for  futher develope the information system. Web-based information system is considered to be a solution in order to acces information faster, systematic cally and easy to use. For that a designed based on information system in the management of Preharvest Technology in Deli Serdang regency was developed. Preharvest Technology Information System was designed using PHP programming language, MySQL database and the system development Lifecycle (SDLC) method. Keywords : Information Systems, Pre-harvest Technology, Web